2003
DOI: 10.1109/tasc.2003.813013
|View full text |Cite
|
Sign up to set email alerts
|

Long-term operational experience with first siemens 400 kW HTS machine in diverse configurations

Abstract: Siemens has built a synchronous machine consisting of an HTS rotor and an air-cored stator. Rotor cooling is provided by a Gifford-McMahon (GM) "off the shelf" cryocooler, the typical requirement being about 30 W @ 25 K. The machine was designed for a rated power of 380 kW (rated voltage 3 phases 400 V Y), but achieved a maximum continuous power of 450 kW and a short term maximum power of 590 kW at 1500 rpm. In all cases, output power was limited by stator cooling. Characteristic parameters such as reactances,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(37 citation statements)
references
References 2 publications
0
36
0
1
Order By: Relevance
“…However, since synchronous reactance of HTS generator in this design is 0.1 p.u, voltage regulation is a relatively low levels as 3.65% with resistance load. This value is a below level of that of 5% without excitation controls and does not pass PCS [7]. Therefore, it is concluded that the margin for improvement of voltage regulation remains.…”
Section: Electrical Characteristics Analysis Of a 10-mw-class Hts Synmentioning
confidence: 81%
“…However, since synchronous reactance of HTS generator in this design is 0.1 p.u, voltage regulation is a relatively low levels as 3.65% with resistance load. This value is a below level of that of 5% without excitation controls and does not pass PCS [7]. Therefore, it is concluded that the margin for improvement of voltage regulation remains.…”
Section: Electrical Characteristics Analysis Of a 10-mw-class Hts Synmentioning
confidence: 81%
“…The difference in the cost of these cooling systems can be consider marginal with respect to the overall cost of the system and it will be mainly related to the efficiency in the thermal insulation. A liquid neon based cooling system with additional thermosyphon has been recently used by Siemens in a prototype superconducting motor [7]. Today the liquid neon is very costly mainly due to its very limited market; but now there are signals that the cryogenic industry can substantially reduce its cost by introducing large liquefaction plants [8].…”
Section: Discussionmentioning
confidence: 99%
“…The first machine was 400kW, 1500rpm with HTS field windings made from 1G BSCCO coils, with a slotless armature winding [34]. The machine was operated at 25K, cooled by a GM cryocooler placed outside the machine, where liquid neon served as the cooling medium [35].…”
Section: Hts Machine Demonstratorsmentioning
confidence: 99%